Responding to The Challenges of The 2045 Golden Generation: Improving a Legal-Aware Golden Generation with a Cultural and Identity Education Approach - Aprillio Poppy Belladonna; Yayuk Hidayah; Neneng Tripuspita (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The golden generation aware of the law is a reality that must be pursued by the people of Indonesia, considering the strong influence of globalization and the positive and negative impacts on the Indonesian nation. This study aimed to explore, study, and obtain an overview of increasing the legal awareness of the golden generation in culture and identity in responding to the challenges of the 2045 golden generation. The method used in this study was a qualitative approach using the case study method. The research location was STKIP Pasundan, Cimahi. Primary data were obtained from purposively selected sources of informants. Secondary data were obtained from library sources. They collect data using interviews, observation, documentation, and literature studies. The research results showed: (1) The strategy for increasing the golden generation to answer the challenges of the 2045 golden generation is to increase morality and creativity in the digital era through Citizenship Education Learning which teaches creativity in the digital era so that a law-aware culture is formed. (2) Improving the legal-aware golden generation is also carried out by strengthening their national identity, namely by various perspectives from a legal, entrepreneurial, and health perspective, and to create a legal-aware, creative, and planning-generation golden generation in 2045. This study was to increase the legal awareness of the golden generation to answer the challenges of the 2045 golden generation, which is a strategic step because it can increase student citizenship knowledge so that there is alignment between civic knowledge, civic skills, and civic disposition.